2022
DOI: 10.1007/s40266-022-00959-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Effectiveness, and Immunogenicity 6 Months After BNT162B2 mRNA Vaccine in Frail Nursing Home Residents

Abstract: Background Elderly people who reside in long-term care facilities form a frail and vulnerable population, with multiple pathologies and high percentages of cognitive and functional disability. Objectives The aims of this study were to assess the safety of vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in frail nursing home residents and to evaluate its effectiveness 6 months after full vaccination. Design Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Among them, the mRNA vaccine mRNABNT162b2 (Comirnaty ® ) has been widely employed in the Italian population ( 4 ). Several studies showed that mRNA vaccines help protect from severe COVID-19 disease, hospitalization and death in immunocompetent individuals and in frail populations ( 5 , 6 ). However, multiple sclerosis (MS) disease modifying therapies (DMTs) might affect COVID-19 disease severity as well as the development of humoral and cellular immunity after SARS-CoV-2 exposure or vaccination ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the mRNA vaccine mRNABNT162b2 (Comirnaty ® ) has been widely employed in the Italian population ( 4 ). Several studies showed that mRNA vaccines help protect from severe COVID-19 disease, hospitalization and death in immunocompetent individuals and in frail populations ( 5 , 6 ). However, multiple sclerosis (MS) disease modifying therapies (DMTs) might affect COVID-19 disease severity as well as the development of humoral and cellular immunity after SARS-CoV-2 exposure or vaccination ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the evidence for the evaluation of SGLT2 inhibitors for the treatment of heart failure originates from large RCTs including many older adults, in which the overall benefit of using dapagliflozin [ 31 ] or empagliflozin [ 29 ] in older patients with heart failure was shown, and the strength of these trials can be considered as Level B [ 30 ] (or level B-R [ 36 ]). Nevertheless, due to the exclusion of older people (especially the frail elderly and residents of long-term care facilities [ 37 ]) from clinical trials, the strength of the evidence for other medications included in the FORTA lists is still widely based on consensus of the participating experts and/or small studies, retrospective studies, or registries. Future RCTs and meta-analyses are still urgently needed to improve the level (quality) of evidence and the related assessments for a large number of substances.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 114 patients with long COVID syndrome, 22.6% reported persistent headaches [3]. Likewise, 7.3% of 137 frail nursing home residents reported headaches 6 months after primary vaccination [4]. Headaches in long COVID and PACVS may have a different character, treatment need and response, and outcome than headaches in acute SC2I or ACVS.…”
Section: Headaches During/after Sars-cov-2 Infection/vaccination Can ...mentioning
confidence: 99%